2022
DOI: 10.3390/safety8030065
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Characteristics of Fire Incident on 24 July 2021 in Jilin Province, China

Abstract: At 15:48 on 24 July 2021, a fire accident occurred in Changchun City, Jilin Province, China, resulting in 15 deaths and 25 injuries. After the accident happened, Jilin Province comprehensively organised an emergency rescue, saving more than 100 trapped people. Given the dangers posed by these events, it is recommended that we must strengthen our risk awareness. Combined with the general background and scene of the fire, in this study, we analysed the causes of the accident and described the on-site rescue acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…According to China's Fire and Rescue Administration statistics, in 2021, electrical fires accounted for the highest proportion of residential fires [2]. Their main cause was the ignition of combustible materials due to electrical circuit faults [6,31]. In addition, this study also found that improper storage of large quantities of flammable materials (UC01) produced large amounts of toxic and harmful gases that helped the spread of fires.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…According to China's Fire and Rescue Administration statistics, in 2021, electrical fires accounted for the highest proportion of residential fires [2]. Their main cause was the ignition of combustible materials due to electrical circuit faults [6,31]. In addition, this study also found that improper storage of large quantities of flammable materials (UC01) produced large amounts of toxic and harmful gases that helped the spread of fires.…”
Section: Discussionmentioning
confidence: 87%
“…Cont. ,3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17,18,19,20,21,22,23,24,26,27,29,30,31,32,33,34,35, 38, 39 4, 7, 11, 29, 33, 34, 36, 38, 39, 40, 41, 42, 43, 44 33, 34, 4, 38, 7, 39, 11, HUB07 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 27, 29, 30, 31, 32, 33, 34, 35, 38, 39 4, 7, 11, 29, 33, 34, 36, 38, 39, 40, 41, 42, , 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 27, 29, 30, 31, , 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 27, 29, 30, 31, 32, 33, 34, 35, 38, 39 4, 7, 11, 29, 33, 34, 36, 38, 39, 40, 41, 42, 43, 44 33,34, 4, 38, 7, 39, 11, SMS04 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 27, 29, 30, 31, 32, 33, 34, 35, 38, 39 4, 7, 11, 29, 33, 34, 36, 38, 39, 40, 41, 42, , 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 26, 27, 29, 30, 31, 32, 33, 34, 35, 38, 39, 44 44 44…”
mentioning
confidence: 99%
“…Based on the conducted investigation, the cargo of 2750 tons of ammonium nitrate was inadequately stored for 6 years without the application of appropriate safety and fire protection measures. In 2021, at least fourteen people died and twelve were seriously injured in a fire that occurred in a logistics warehouse located in Changchun [7], the capital of the northeastern province of Jilin. At least 49 people, including 9 firefighters, were killed in a major fire in 2022 at a container warehouse near a port city in southeastern Bangladesh [8], and more than 100 people were injured in total.…”
Section: Introductionmentioning
confidence: 99%